2021
DOI: 10.3389/fgene.2021.611442
|View full text |Cite
|
Sign up to set email alerts
|

NPC2 as a Prognostic Biomarker for Glioblastoma Based on Integrated Bioinformatics Analysis and Cytological Experiments

Abstract: Glioblastoma (GBM) is one of the most common and fatal malignancies worldwide, while its prognostic biomarkers are still being explored. This study aims to identify potential genes with clinical and prognostic significance by integrating bioinformatics analysis and investigating their function in HNSCC. Based on the Single-cell RNA sequencing (scRNA-seq) results of H3K27M-glioma cells, computational bioinformatics methods were employed for selecting prognostic biomarker for GBM. The protein NPC2 (NPC Intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…A large number of the genes in this model were closely related to the immune response. For example, NPC2 is involved in the lipoprotein metabolism and innate immune signal pathways,38…”
mentioning
confidence: 99%
“…A large number of the genes in this model were closely related to the immune response. For example, NPC2 is involved in the lipoprotein metabolism and innate immune signal pathways,38…”
mentioning
confidence: 99%
“…LDL-derived cholesterol trapped in lysosomes imitates the absence of cholesterol uptake, thus inducing the inhibition of cell viability [68]. Since a study has demonstrated that NPC2 is an unfavorable prognostic biomarker in GBM [69], NPC2 may also become a potential target for the treatment of GBM. Ríos-Marco et al found that alkylphospholipids such as perifosine, edelfosine, erucylphosphocholine (ErPC) and hexadecylphosphocholine (HePC) interfere with cholesterol trafficking from the plasma membrane to the endoplasmic reticulum, hindering cholesterol esterification.…”
Section: Disruption Of Cellular Cholesterol Traffickingmentioning
confidence: 99%
“…A CCK-8 assay was conducted as per our previous study (30). Briefly, cellular viability was determined using a CCK-8 (Beyotime Biotechnology).…”
Section: Cell Counting Kit-8 Assay (Cck-8)mentioning
confidence: 99%
“…A wound-healing assay was conducted as per our previous study (30). Briefly, DBTRG and U251 cells were seeded in a 6-well plate evenly with the cell concentration of 1×10 6 per well.…”
Section: Wound-healing Assaymentioning
confidence: 99%
See 1 more Smart Citation